Different imaging characteristics of concurrent pituitary adenomas in a patient with Cushing's disease. Issue 5 (May 2015) - Mehta, Gautam U.; Montgomery, Blake K.; Raghavan, Pooja; Sharma, Susmeeta; Nieman, Lynnette K.; Patronas, Nicholas; Oldfield, Edward H.; Chittiboina, Prashant
Abstract We report a patient with Cushing's disease (CD) and two pituitary adenomas that demonstrated different imaging characteristics and therefore suggest an alternative imaging strategy for these patients. A 42-year-old woman presented with signs and symptoms of CD. Biochemical evaluation confirmed hypercortisolemia and suggested CD. On pituitary MRI with spoiled gradient recalled acquisition in the steady-state and T1-weighted spin echo protocols, a 5 mm hypoenhancing region typical for a pituitary adenoma was identified on the left. However, after surgical resection the patient remained hypercortisolemic and pathology revealed a non-functional adenoma. At early repeat surgical exploration a 10 mm adenoma was found in the right side of the gland. Postoperatively the patient became hypocortisolemic and pathology demonstrated an adrenocorticotropic hormone (ACTH)-staining adenoma. On review of the initial MRI this tumor corresponded to a region of contrast retention best visualized on delayed fluid attenuated inversion recovery (FLAIR) imaging. While the incidentaloma in this case demonstrated classical imaging characteristics of a pituitary adenoma the larger ACTH-secreting tumor was best appreciated by contrast retention. This suggests a role for delayed postcontrast FLAIR imaging in the preoperative evaluation of CD. ACTH-secreting tumors causing CD cause significant morbidity. Due to their small size, a pituitary adenoma is frequently not identified on imaging despite endocrinologic testing suggesting CD. Regardless of improvements in MRI, many tumors are only identified at surgical exploration.